Power, pleasure, and profit insatiable appetites from Machiavelli to Madison - Wootton, David, 1952- (The Belknap Press of Harvard University Press, 2018)
"We pursue power, pleasure, and profit. We want as much as we can get, and we deploy instrumental reasoning--cost-benefit analysis--to get it. We judge ourselves and others by how well we succeed. It is a way of life and thought that seems natural, inevitable, and inescapable. As David Wootton shows, it is anything but. In Power, Pleasure, and Profit, he traces an intellectual and cultural revolution that replaced the older normative systems of Aristotelian ethics and Christian morality with the iron cage of instrumental reasoning that now gives shape and purpose to our lives. Wootton guides us through four centuries of Western thought--from Machiavelli to Madison--to show how new ideas about politics, ethics, and economics stepped into a gap opened up by religious conflict and the Scientific Revolution. As ideas about godliness and Aristotelian virtue faded, theories about the rational pursuit of power, pleasure, and profit moved to the fore in the work of writers both obscure and as famous as Hobbes, Locke, and Adam Smith. The new instrumental reasoning was a double-edged weapon. It cut through old codes of status and rank, enabling the emergence of movements for liberty and equality. But it also helped to create a world in which virtue, honor, shame, and guilt count for almost nothing, and what matters is success.--